Self-Perceptions of Older Never-Married Women in a Fluid and Changing Asian Society: A Narrative Inquiry - Manalo, Maria Tamara Isabelle M. (Archīum Ateneo, 2021)
As one of the strongly devout Catholic countries in Southeast Asia, the Philippines recognizes marriage as a paramount social institution, where unmarried women face negative perceptions and social consequences. With the increasing populace of elderly people in the country, this study focused on the conditions of middle-aged (ages 45 to 65) never-married women and how the family-oriented society construes their self-perceptions. By interviewing 24 older never-married women over the age of 45, four key aspects were identified behind their lived experiences: interest in marriage, engagement in relationships, societal change, and ending in acceptance. Results open the discussion for social and individual implications.